What strategies can Egyptian non-governmental organizations apply to ensure financial sustainability? - Gaber, Amira Hussein (AUC Knowledge Fountain, 2017)
Financial challenges have serious implications on the sustainability of non-governmental organizations (NGOs). This study addresses the instabilities experienced by Egyptian NGOs. The research explores the internal and external challenges hindering the sustainability of these associations and the weaknesses within the organizations as well. Additionally, the study investigates the chances of NGOs for financial survival, given the waning of funding and the legal, regulatory framework under which they operate. The case studies presented includes two Egyptian associations that were able to strive and flourish, despite funding limitations. The analysis conducted highlights their similarities and differences in terms of types of services, method of operation, and the fundraising strategies that enabled them to remain sustainable amidst these challenges. Building a niche without monetary grants and working with donors on partnership basis have been NGO1’s main tool. NGO2, on the other hand, applied strong marketing techniques and developed a sustainable business model. Special outreach and networking capabilities, efficient operations, awardees selections and the diversification of its portfolio of sponsors and volunteers contributed to the sustainability of both organizations.